2013
DOI: 10.1371/journal.pone.0060220
|View full text |Cite
|
Sign up to set email alerts
|

Human Protein Cluster Analysis Using Amino Acid Frequencies

Abstract: The paper focuses on the development of a software tool for protein clustering according to their amino acid content. All known human proteins were clustered according to the relative frequencies of their amino acids starting from the UniProtKB/Swiss-Prot reference database and making use of hierarchical cluster analysis. Results were compared to those based on sequence similarities. Results: Proteins display different clustering patterns according to type. Many extracellular proteins with highly specific and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
(10 reference statements)
0
4
0
Order By: Relevance
“…The protein sequences in FLAT file format were downloaded from UniProtKB/Swiss-Prot protein database (http://www.uniprot.org/uniprot/). A software tool [2] was applied to the data contained in the FLAT file of the protein. The SQ section of the FLAT file was used to compute the absolute and the relative frequencies of all AAs contained in the protein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The protein sequences in FLAT file format were downloaded from UniProtKB/Swiss-Prot protein database (http://www.uniprot.org/uniprot/). A software tool [2] was applied to the data contained in the FLAT file of the protein. The SQ section of the FLAT file was used to compute the absolute and the relative frequencies of all AAs contained in the protein.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study [2], we found several evidences that the composition of proteins gives information on AA availability and local control of protein expression. The study compared human proteins on the basis of their AA content by a hierarchical, agglomerative clustering method.…”
Section: Introductionmentioning
confidence: 99%
“…Substitution models of evolution describe the process of genetic variation through fixed mutations and constitute a basis of the evolutionary analysis on the molecular level [2] . Yet, the focus on the manifestation of amino acid changes (or amino acid frequencies [29] does not account for the circumstance that selection and self-organization favor certain mutations over others (natural selection could have acted in sequence space to select non-random sequences satisfying the requirement for a large energy gap between native and unfolded conformations [23] . Notably, such accounting has become principally feasible over the past years, in which a substantial body of knowledge has been accrued to describe the physical and chemical properties of amino acids.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding participants' behavioral patterns and learning about commonalities and diversities in these is a challenging task. These types of analyses were done in past for many fields, such as usability research using machine learning, data mining (Paliouras, Papatheodorou, Karkaletsis, & Spyropoulos, 2002), grouping of users for music recommendation (Chen & Chen, 2001) based on complex amino acid sequences (Vernone, Berchialla, & Pescarmona, 2013). Such application exists also in the field of eye tracking, which is the focus of this paper.…”
Section: Introductionmentioning
confidence: 99%